Healthy Herbal Teenagers: Reproductive Health Improvement Strategies at SMK Bhakti Asih - Harmatuti, Harmatuti; Aurelia, Putri Yasyfa (Jurnal Indonesia Sosial Sains, 2025)
Adolescent reproductive health is one of the important issues in community health development. Low knowledge and unhealthy lifestyles can trigger various problems, such as anemia, dysmenorrhea, and hormonal disorders. The "Herbal Healthy Youth" program is designed to improve the understanding and practice of healthy lifestyles through education, the use of herbal plants, and mentoring at SMK Bhakti Asih. This study uses the quasi-experimental method with the pretest-posttest design involving 60 students. The results showed a significant increase in reproductive health knowledge by 40% and decreased menstrual pain complaints in students by 35%. In conclusion, herbal -based reproductive health education is effective in increasing awareness and healthy behavior of adolescents.